Fixed Prosthodontic Learning Dossier Assignment - Vanessa Swain; Noriko Boorberg (Association of American Medical Colleges, 2009)
Abstract Introduction This learning dossier assignment is a didactic evaluation tool for dental students in the early stages of their clinical experiences in fixed prosthodontics. The two processes that characterize learning dossiers are reflection and inquiry. Portfolio assessments have been shown to be a valid and reliable method to assess student competency in dental fields. This assignment is an alternative to traditional didactic tests relying on rote memory. Its goal is to encourage thinking and learning on higher levels, resulting in well-integrated experiential knowledge regarding fixed prosthodontics. Methods The assignment is given to students at the beginning of the academic year in a paper folder. Included in the assignment are a brief description of the rationale, detailed instructions for completion of the assignment, student checklists, and the scoring rubrics for each of the four sections (treatment planning, cores, crowns, and an end-of-year reflection on the learning process). Instructions state that student reference materials and instructor grading rubrics must be on on yellow-colored paper, while all student materials to be filled out or added to the dossier should be on white paper. All materials are kept cumulatively in the dossier throughout the year. Students will require access to their patient charts for the purpose of duplicating radiographs, photographs, and other pertinent information. Clarification within individual institutions will be needed regarding the policies for use of patient information prior to implementing this project. Students are asked to use critical thinking and problem-solving skills to construct meaning from their educational experiences in the four sections noted above. Results This project is currently in use for its third year and has undergone small refinements each year. Students who completed the assignment reported satisfaction with having no traditional didactic test involving rote memorization and regurgitation; they felt that overall, the assignment provided a positive learning experience. Students also appreciated the organized structure and well-defined grading rubric that they had access to while completing the dossier. From an instructor viewpoint, while there is a range in the overall quality of the assignments assessed, many are high-quality submissions demonstrating synthesis of information from clinical experiences, lectures, and the dental literature that would be difficult to achieve through other, more traditional teaching modalities. Discussion Although the dossier project is more useful than traditional exams at integrating clinical knowledge, it does have the disadvantage of increasing the time required for instructor evaluations. The process can be facilitated by ensuring that all materials relevant to the cases discussed (from treatment plans and radiographs to journal article abstracts) are included as part of each student's dossier. This assignment allows students to reflect on their clinical experiences and aids in both the evaluation of their work and the integration of knowledge from the dental literature with the clinical decisions students made.